Interação mãe-crianças gêmeas com Transtorno do Espectro Autista : análise dos comportamentos comunicativos - Miranda, Fernanda da Silva (2021)
The present study aimed to analyze interactions between a mother and her twin children with Autist Spectrum Disorder (ASD) in free-play situations.Communicative styles used by the mother when dealing with the children were specifically identified, as well as their participation and responses to maternal speech in this interactive context. A mother and her 4-year-old twin children of the male gender, diagnosed with ASD, took part in this study; both of whom with a severe level of impairment, according to the CARS (Childhood Autism Rating Scale) applied with the mother.A semi-structured interview was also accomplished so as to collect sociodemographic data about the mother and the twin children, as well as the ASD diagnostic process, the children’s routines/activities, and the maternal conceptions with regard to their development; then, observations in the family’s residence in free-play situations were made, as registered on footages with a digital-video camera. In this procedure, the children were observed with the mother separately, for 20 minutes. The data analysis was done as of the transcription of the mother’s interview and the transcription of the observations, following the norms of the CHILDES (Child Language Data Exchange System) computer program. The results pointed out that the mother’s verbal communicative styles most frequently presented to the twins during the free-play sessions were the directive ones, followed by requests. The analyses concerning the directive types which prevailed in the maternal speech revealed that, with both twins, the directives of instruction and the ones of attention were the most used ones, indicating that, intent on interacting with the children, the mother aimed to lead them to be engaged with the activities and plays mostly by means of commands and requests so that they could be able to participate in the proposed activities. Where the children’s communicative behaviors are concerned, the twins showed a higher rate of inadequate non-verbal responses to the maternal speech, occurring in the moments that they showed refusal and lack of interest in the proposed activities, whether they were presented or requested, in addition to distractions in other activities. However, these outcomes were problematized, taking into account that the children are within the autist spectrum. Still, it is worthwhile highlighting that the fact that the present study was carried out with the two twin children with ASD interacting separately with their mother made it possible to assess more precisely the maternal communicative styles towards them, and how these styles are influenced not only by the playing context in which they are found but also by each child’s own characteristics. Furthermore, it is expected that this study will contribute for a better understanding when it comes to maternal communicative styles towards children with ASD in the contexts of both interaction and participation of children in this interactive process, considering that they have impairments both in the communicative dimension and social interaction. Thus, the comprehension of the peculiar ways by which these children settle their relationships and communicate will contribute in the direction that, within this interactive context, mothers will be well able to respond to them according to their particularities, favoring their development.